2021
DOI: 10.1136/rmdopen-2021-001925
|View full text |Cite
|
Sign up to set email alerts
|

Role of targeted therapies in rheumatic patients on COVID-19 outcomes: results from the COVIDSER study

Abstract: ObjectivesTo analyse the effect of targeted therapies, either biological (b) disease-modifying antirheumatic drugs (DMARDs), targeted synthetic (ts) DMARDs and other factors (demographics, comorbidities or COVID-19 symptoms) on the risk of COVID-19 related hospitalisation in patients with inflammatory rheumatic diseases.MethodsThe COVIDSER study is an observational cohort including 7782 patients with inflammatory rheumatic diseases. Multivariable logistic regression was used to estimate ORs and 95% CIs of hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Fever (67% vs. 57%), cough (57% vs. 42%), dyspnea (34% vs. 20%), myalgia (76% vs. 62%), loss of taste and smell (54% vs. 21%), and lung involvement (28% vs. 14%) were found to be significantly lower in the omicron period patients (p<0.05 for all). Our results are in line with previous studies on this subject (3)(4)(5)(6)(7)(8)(9). Santos et al from Spain, reported the presence of rheumatic disease activity, dyslipidaemia, and cardiovascular disease as risk factors for mortality in a study they conducted in the first months of the pandemic (3).…”
supporting
confidence: 92%
“…Fever (67% vs. 57%), cough (57% vs. 42%), dyspnea (34% vs. 20%), myalgia (76% vs. 62%), loss of taste and smell (54% vs. 21%), and lung involvement (28% vs. 14%) were found to be significantly lower in the omicron period patients (p<0.05 for all). Our results are in line with previous studies on this subject (3)(4)(5)(6)(7)(8)(9). Santos et al from Spain, reported the presence of rheumatic disease activity, dyslipidaemia, and cardiovascular disease as risk factors for mortality in a study they conducted in the first months of the pandemic (3).…”
supporting
confidence: 92%
“…According to our observation, vaccination appears to be the greatest protective factor towards COVID-19. Unlike previous reports in the context of rheumatic diseases [ 5 ], no major or fatal COVID-19-related complications were reported in our patients receiving rituximab: our therapeutic scheme is limited to a single infusion of 375 mg/m 2 and this strategy may protect against severe complications.…”
mentioning
confidence: 55%
“…The COVIDSER study is an observational cohort of patients from three Spanish database registries which included patients with rheumatic diseases: BIOBADASER III, CARMA and RELESSER, all promoted by the Spanish Society of Rheumatology. 15 In this study, only patients from BIOBADASER III were included. BIOBADASER is a Spanish multicentre observational registry used to assess safety in patients with rheumatic diseases who start treatment with any targeted therapy, including bDMARDs, biosimilars or tsDMARDs.…”
Section: Methodsmentioning
confidence: 99%
“…The COVIDSER study is an observational cohort of patients from three Spanish database registries which included patients with rheumatic diseases: BIOBADASER III, CARMA and RELESSER, all promoted by the Spanish Society of Rheumatology 15. In this study, only patients from BIOBADASER III were included.…”
Section: Methodsmentioning
confidence: 99%